2018
DOI: 10.1084/jem.20181402
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical assembly and disassembly of a transcriptionally active RAG locus in CD4+CD8+ thymocytes

Abstract: Expression of Rag1 and Rag2 is tightly regulated in developing T cells to mediate TCR gene assembly. Here we have investigated the molecular mechanisms governing the assembly and disassembly of a transcriptionally active RAG locus chromatin hub in CD4+CD8+ thymocytes. Rag1 and Rag2 gene expression in CD4+CD8+ thymocytes depends on Rag1 and Rag2 promoter activation by a distant antisilencer element (ASE). We identify GATA3 and E2A as critical regulators of the ASE, and Runx1 and E2A as critical regulators of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…At the core of the recombination machinery are the RAG proteins 15 . The RAG gene locus, comprising RAG1 and RAG2, has been reported to be coordinately regulated by RUNX proteins and we confirm here Runx1 binding to the Rag1 core promoter 32,33 . The transcription factor RUNX1 is also involved in the regulation of T-cell-specific genes such as CD4 and CD8 23,34 .…”
Section: Discussionsupporting
confidence: 83%
“…At the core of the recombination machinery are the RAG proteins 15 . The RAG gene locus, comprising RAG1 and RAG2, has been reported to be coordinately regulated by RUNX proteins and we confirm here Runx1 binding to the Rag1 core promoter 32,33 . The transcription factor RUNX1 is also involved in the regulation of T-cell-specific genes such as CD4 and CD8 23,34 .…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have identified several cis-regulatory elements in the Rag1/2 gene locus, including the anti-silencing element (ASE) and enhancer of Rag (Erag) (12,13). Deletion of these elements resulted in the partial loss of RAG1 and RAG2 activity, suggesting the presence of additional regulatory elements for Rag1/2 gene expression (5,(13)(14)(15). Besides, what TFs regulate these regulatory elements for Rag gene expression during T and B cell development remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by using the VL3-3M2DP thymocyte cell line, this group demonstrated that the ASE requires Gata3 and E2A, while the Rag1 promoter relies on Runx1 and E2A as critical regulators. Together, the ASE and Rag1 promoter framework functions as a chromatin hub ( 65 ). Recently, we have identified cell type-specific CREs for Rag1/2 expression in B and T cells using E2A ChIP-seq and ATAC-seq data, because E2A specifies adaptive lymphocyte and is the driver of differences in enhancer repertoires in T cells and ILCs ( 24 , 52 ).…”
Section: The Regulation Of Rag1/2 Expression By CImentioning
confidence: 99%